The Effect of Using Videos and Photovoice on the Students' Achievement in Writing Explanation Text - Ifa Amalia Anwar (Language-Edu, 2021)
This study aims to explore the effectiveness of using videos and photovoice on the students’ achievement in writing Explanation text. It is a quasi-experimental design which involves 70 students of MAN 1 Banyuwangi in 2020/2021 academic year. XI MIPA 1 as the control group and XI MIPA 2 as the experimental group. These two groups were proved on the same level of writing ability by the score of pre-test. There were six meeting in this research, a meeting for pre-test, four meetings for the treatment through E-Learning Madrasah, and a meeting for post-test. The data obtained were analyzed by using independent t-test formula. The result showed that the t-value =-2.729, p =.008 and the results indicated that there is significant difference after having treatment by using videos and photovoice since p =.008 is less than 0.05.  Based on the result of data analysis, the eleventh grade students of MAN 1 Banyuwangi who were taught by using videos and photovoice achieve better score on writing Explanation text than those who were taught by using PowerPoint.Keywords: videos, photovoice, explanation text